Enthüllte Göttinnen: der Blick des Dichters (Ovid und Kallimachos) - Leidl, Christoph (Antike Erzähl- und Deutungsmuster, 2018)
The tension between narrative and vision (both as the poet’s imagination preceding the text, as textualised description of the visible within the text, and as the vision created in the reader through the text) is not only a matter of literary technique, but, as is argued in the article, can also create disruptions on the thematic level of the text, in the narrative detail. The texts investigated are the Actaeon-episode in Book 3 of Ovid’s Metamorphoses, the Venus-Verticordia report from his Fasti, Amores 1.5, and Callimachus’ Hymn 5 (Εἰς λουτρὰ τῆς Παλλάδος). Beyond the now almost conventional poetological interpretation of the Ovidian text, particular emphasis is placed upon the way in which Ovid’s Actaeon combines traits of Callimachus’ Teiresias and Actaeon, and in the way Ovid goes even further than Callimachus in placing the moment of the contact between god and man, the divine epiphany, almost beyond any possibility of sensual perception (and verbal description). A comparison with modern poetical transformations (Hughes 1997) or visual representations only emphasizes Ovid’s exceptional focus in this scene. Ovid’s version amounts to an analysis of basic poetical (or even human) activities (further developing Callimachean ideas): seeing and speaking. Despite the plot of the Actaeon story and Ovid’s lavish use of visualizing literary techniques in the passage, Actaeon’s gaze is not mentioned as actively directed towards Diana, but at himself (like Narcissus). At their meeting, Diana and Actaeon in turn are veiled and unveiled, so that the tables are turned and Actaeon becomes the object of the gaze. It is at this moment that he loses his speech (and thus the use of his name). This can be seen as an analogy to the relationship between the poet’s perception and his ability to express it verbally and his presence or absence in text. If Callimachus’ Hymn 5 could be interpreted as a kind of poetical initiation (Dichterweihe), as suggested by Müller (1987), Ovid - supposedly taking his cue from this possible interpretation - would have formed an inverse initiation in his Actaeon story, an initiation which makes the poet as a real person disappear. The combination of traits from Ovid’s own Actaeon in the Metamorphoses with a rewriting of the ritual in Callimachus results in his construction of a festival for Venus Verticordia on 1 April in Fasti 4. Ovid gives the stories of Teiresias and Actaeon a new turn: veiling and unveiling have opposite (positive sexual) meanings. In this literary reconstruction of Greek myth and literature, Venus takes on not only literary responsibilities, but also new political functions in Augustan Rome. All this is not the faithful representation of Roman ritual, but a result of Ovid’s poetic imagination, expressed in a new literary form. Only in his earlier work (Ov. Am. 1.5) had the poet’s gaze at an unveiled goddess (Corinna) been without danger. Callimachus has served Ovid as catalyst in the reflection on seeing and (un)veiling as communicative problems and on the poet’s power to create myth and unifying ritual from his imagination.
Gesehen am 26.07.2019